PERANCANGAN SISTEM INFORMASI PENJUALAN PRANGKO PRISMA DIKANTOR POS KCU BANDUNG BERBASIS WEB - Anas Anugrah Perdana; Diski Malikal Mulki; Riky Faza (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2022)
AbstractThis research aims to analyze, design and create a Prisma Stamp ordering information system based on case studies at PT. Pos Indonesia KCU Bandung. Data collection techniques are using observation and interview methods. The software design method used is waterfall. The results of observations made, there are several factors that hamper the sales system of stamps and prisms because they still use manual means using notes and then the sales report is entered into the sales report file that is considered less effective and efficient, therefore, there are often errors at the time of recording transactions. Therefore, in this study created a postage stamp and prism sales system using Unified modeling language and implemented it using codeigniter framework with PHP programming language and MySQL database. The web-based information system is expected to facilitate transactions and expand the prism stamp sales network over the internet and allow administrators to manage product data and view sales reports easily, quickly, and accurately.Keywords: Information System, UML, Web